2014
DOI: 10.1021/jp501819p
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation Synthesis of Blue TiO2 for High-Performance Lithium-Ion Batteries

Abstract: Blue hydrogenated rutile TiO 2 nanoparticles (blue TiO 2 ) are prepared by treating white rutile via an enhanced hydrogenation process (i.e., high pressure and temperature). The materials characterization results demonstrate that the hydrogenation process leads to the increase in the unit cell volume and decrease in the size compared with the untreated white TiO 2 . The electrochemical impedance spectra analyses and theoretical energy calculations using density functional theory (DFT) suggest that the hydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
151
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(156 citation statements)
references
References 31 publications
5
151
0
Order By: Relevance
“…These results show that a slight change occurred along the a and b directions, but there was significant expansion in the c direction, and as a result, the unit cell volume expanded significantly as well [10]. Recent publications showed that the morphology of TiO 2 materials resulted in differences of the enhanced photocatalytic activity for the production of hydrogen between the {101} and {001} facets of anatase tetragonal bipyramidal nanocrystals [11][12][13].…”
Section: General Structure and Properties Of Tiomentioning
confidence: 73%
See 2 more Smart Citations
“…These results show that a slight change occurred along the a and b directions, but there was significant expansion in the c direction, and as a result, the unit cell volume expanded significantly as well [10]. Recent publications showed that the morphology of TiO 2 materials resulted in differences of the enhanced photocatalytic activity for the production of hydrogen between the {101} and {001} facets of anatase tetragonal bipyramidal nanocrystals [11][12][13].…”
Section: General Structure and Properties Of Tiomentioning
confidence: 73%
“…In both structures, the octahedral distortions create the basic building units [7,8]. The lengths and angles of octahedral coordinated Ti atoms, therefore, dictate stacking in both structures, as shown in Figure 1. 3.…”
Section: General Structure and Properties Of Tiomentioning
confidence: 99%
See 1 more Smart Citation
“…1.5 nm. This surface lattice disorder which can be attributed to the hydrogenation treatment could yield mid-gap electronic levels that are responsible for the absorption of broader light wavelengths [27]. While the TiO2 electrode strongly absorbs light only in the UV region due to the large band gap (3.0 eV for rutile), the Au@TiO2 electrode shows another absorption band centered at 560 nm that can be attributed to the typical SPR effect of Au nanoparticles.…”
Section: Characterization Of Photoelectrodesmentioning
confidence: 99%
“…[25,49,61] Meanwhile, there are a few reports mentioning possible decrease in the photocatalytic activities, if the hydrogenated TiO 2 nanomaterials are not properly prepared. [37,38] So far, hydrogenation has been conducted on TiO 2 nanoparticles, [4,21,31] nanorods, [48] nanotubes, [45] nanowires, [46] nanosheets, [35,36] with anatase or rutile phase, [4,29,33] under high-pressure, [4,21] ambient pressure, [29,30,39] or low-pressure [43] pure hydrogen environment, or hydrogen-argon, [44][45][46][47][48] hydrogen-nitrogen [52][53][54] gas flow, in the temperature range from room temperature [21] to 700°C, [27] with a hydrogenation time from a few minutes [27] to 20 days. [21] With no doubt, we can image that the so-formed TiO 2 nanomaterials will display variations in their characteristics and performances.…”
Section: +mentioning
confidence: 99%